Surface functionalization of cellulose nanocrystals with polymeric ionic liquids during phase transfer. (10th February 2017) - Huang, Shuohan; Wang, Xinhang; Shen, Jiahao; Wu, Routeng; Zhao, Hualei; Wang, Yanping; Wang, Yimin; Xia, Yumin
Highlights: Poly(ionic liquid) (PIL) was able to transport CNCs from aqueous phase to apolar organic phase. PIL has strong interactions with CNCs and these interactions are noncovalent. Through these interactions, PIL can modify CNCs and change the surface amphipathicity. PIL-modified CNCs can be dispersed in low polar organic solvents which pristine CNCs couldn't. This method is significant to broaden application of CNCs in nanocomposite materials. Abstract: In this study, the cellulose nanocrystals (CNCs) were prepared by method of acid hydrolysis, while the polymeric ionic liquid (PIL) [PEP-MIM]DBS was synthesized by epichlorohydrin, o -phthalic anhydride as well as N -methylimidazole then anion exchanged by sodium dodecyl benzene sulfonate. It was demonstrated that [PEP-MIM]DBS could modify CNCs by non-covalent interaction to change its surface properties, such as amphiphilicity. The chemical structure of the composite CNCs/[PEP-MIM]DBS was characterized via FTIR, 13 C NMR, TGA, XRD, etc. Moreover, the properties and applications were characterized through a series of dispersion experiments, contact angle tests, FE-SEM, etc. This study showed that the PIL-modification improved the dispersion of CNCs in non-polar organic solvents with their chemical structure integrated.